2020
DOI: 10.5530/pj.2020.12.4
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Soursop Leaves (Annona muricata) against Cervical HeLa Cancer Cells

Abstract: Background: Cervical cancer is the cancer with highest prevalence and the leading cause of women death in Indonesia. Current treatments available for cervical cancer are chemotherapy, radiation, surgery, and nuclear therapy. Unfortunately, these treatments still have several limitations due to serious side effects, development of resistance, and very expensive price. Therefore, it is necessary to develop effective and low-cost therapy to treat cervical cancer. One of which is by utilizing natural sources avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
1
6
1
Order By: Relevance
“…22 In addition, previous studies also showed an increase in the percentage of inhibition in the three fractions along with an increase in the concentration of A. muricata. 12 However, the results of the ethanol fraction in this study were different. The percentage of inhibition of the ethanol fraction of A. muricata at a concentration of 100 µg/mL was 57.64% and then decreased with increasing concentration.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…22 In addition, previous studies also showed an increase in the percentage of inhibition in the three fractions along with an increase in the concentration of A. muricata. 12 However, the results of the ethanol fraction in this study were different. The percentage of inhibition of the ethanol fraction of A. muricata at a concentration of 100 µg/mL was 57.64% and then decreased with increasing concentration.…”
Section: Discussioncontrasting
confidence: 58%
“…In previous studies on the cytotoxicity of A. muricata, ethanol, ethyl acetate and hexane fractions against HeLa cell lines proved that the three fractions were strongly cytotoxic, with IC 50 in the ethanol fraction of 5.91 µg/mL, in the ethyl acetate fraction of 7.56 µg/mL and in the hexane fraction of 8.39 µg/mL. 12 The three values of IC 50 in this study are close to the IC 50 value of the positive control, namely Cisplatin (IC 50 value: 1.78 µg/mL). Cisplatin is one of the well-known chemotherapy drugs and has been used in the treatment of various cancers, one of which is head and neck cancer.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The ASL and ASS oils showed IC 50 values of 190±10.70 and 339±19.00 μg/mL, respectively. The American National Cancer Institute guidelines state that extracts or compounds with IC 50 value <20 μg/mL are recorded as cytotoxic active agents [39] . Accordingly, both essential oils displayed very weak cytotoxic effects on test cell lines and are safe for human use.…”
Section: Resultsmentioning
confidence: 99%